Flexible cobalt hexacyanoferrate/carbon cloth nanocomposites for H2O2 detection. Issue 12 (9th March 2016) - Ye, Yihan; Zheng, Yaolin; Yu, Jie; Zhang, Yayun; Song, Yonghai; Guo, Qiaohui; Wang, Li; Xu, Fugang
Abstract : A flexible nanocomposite of cobalt hexacyanoferrate (CoHCF) and commercial carbon cloth (CC) was prepared by facile electrodeposition of CoHCF on a flexible CC surface. Abstract : A flexible nanocomposite of cobalt hexacyanoferrate (CoHCF) and commercial carbon cloth (CC) was prepared by facile electrodeposition of CoHCF on a flexible CC surface. As a kind of flexible integrated electrode without polymer binders, the flexible CC–CoHCF nanocomposites were directly used for nonenzymatic H2 O2 sensing. Several techniques such as scanning electron microscopy, energy dispersive X-ray spectroscopy, Fourier transform infrared spectroscopy and electrochemistry were employed for the characterization of the electrode. It was found that CoHCF nanoparticles (about 100 nm) uniformly deposited on the CC surface. Electrochemical experiments demonstrated that the flexible CC–CoHCF nanocomposite electrode exhibited good electrocatalytic activity towards the oxidation of H2 O2 . Based on the amperometric experiments, the proposed nonenzymatic sensor showed a linear response to H2 O2 detection in the range of 0.002–9.04 mM with a detection limit of 0.7 μM, which was superior to most of the previous results. Such a good result renders it a promising candidate for routine testing.